Multimonth dispensing of up to 6 months of antiretroviral therapy in Malawi and Zambia (INTERVAL): a cluster-randomised, non-blinded, non-inferiority trial. Issue 5 (May 2021) - Hoffman, Risa M; Moyo, Crispin; Balakasi, Kelvin T; Siwale, Zumbe; Hubbard, Julie; Bardon, Ashley; Fox, Matthew P; Kakwesa, Gift; Kalua, Thokozani; Nyasa-Haambokoma, Mwiza; Dovel, Kathryn; Campbell, Paula M; et al.
Summary: Background: Facility-based, multimonth dispensing of antiretroviral therapy (ART) for HIV could reduce burdens on patients and providers and improve retention in care. We assessed whether 6-monthly ART dispensing was non-inferior to standard of care and 3-monthly ART dispensing. Methods: We did a pragmatic, cluster-randomised, unblinded, non-inferiority trial (INTERVAL) at 30 health facilities in Malawi and Zambia. Eligible participants were aged 18 years or older, HIV-positive, and were clinically stable on ART. Before randomisation, health facilities (clusters) were matched on the basis of country, ART cohort size, facility type (ie, hospital vs health centre), and region or province. Matched clusters were randomly allocated (1:1:1) to standard of care, 3-monthly ART dispensing, or 6-monthly ART dispensing using a simple random allocation sequence. The primary outcome was retention in care at 12 months, defined as the proportion of patients with less than 60 consecutive days without ART during study follow-up, analysed by intention to treat. A 2·5% margin was used to assess non-inferiority. This study is registered with ClinicalTrials.gov, NCT03101592 . Findings: Between May 15, 2017, and April 30, 2018, 9118 participants were randomly assigned, of whom 8719 participants (n=3012, standard of care group; n=2726, 3-monthly ART dispensing group; n=2981, 6-monthly ART dispensing group) had primary outcome data available at 12 months and were included in the primary analysis. The median age of participants was 42·7 years (IQR 36·1–49·9) and 5774 (66·2%) of 8719 were women. The primary outcome was met by 2478 (82·3%) of 3012 participants in the standard of care group, 2356 (86·4%) of 2726 participants in the 3-monthly ART dispensing group, and 2729 (91·5%) of 2981 participants in the 6-monthly ART dispensing group. After adjusting for clustering, for retention in care at 12 months, the 6-monthly ART dispensing group was non-inferior to the standard of care group (percentage-point increase 9·1 [95% CI 0·9–17·2]) and to the 3-monthly ART dispensing group (5·0% [1·0–9·1]). Interpretation: Clinical visits with ART dispensing every 6 months was non-inferior to standard of care and 3-monthly ART dispensing. 6-monthly ART dispensing is a promising strategy for the expansion of ART provision and achievement of HIV treatment targets in resource-constrained settings. Funding: US Agency for International Development.